HUBUNGAN PENGETAHUAN IBU TENTANG PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING DI DESA WONOGRIYO - Jumrotun Nafisah; Muthmainnah Zakiyyah; Nova Hikmawati (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Stunting is a chronic nutritional problem due to lack of nutrition in the long term, resulting in impaired growth in children. The incidence of stunting is caused by low family income, non-exclusive breastfeeding, poor Breastmilk Complementary Food giving, incomplete immunization with the most dominant factor influencing is non-exclusive breastfeeding. A mother should have good knowledge in breastfeeding which will make the mother aware and have a positive attitude about the importance of proper exclusive breastfeeding so that the mother provides good nutrition to her baby. The purpose of this study was to determine the correlation between mother's knowledge about exclusive breastfeeding and the incidence of stunting in Wonogriyo village. The research method was a quantitative analytic study with a cross-sectional study design with 35 respondents, mothers who have children up to 2 years old, using a sampling technique. The instrument used was a questionnaire. The analysis used univariate analysis and bivariate analysis with the Spearman Rank test (Rho). The result of the research is a significant correlation between mother’s knowledge about exclusive breastfeeding and the incidence of stunted with a sig (2-tailed) = 0,704. Then p-value = 0.704 (p<0,05) means that there is a significant correlation between the two variables.